A PRAGMATIC EXAMINATION OF TEACHERS’ SPEECH ACTS IN ENGLISH CLASSROOM INTERACTION - Dewi, Nila Sari; Hartiwi, Juni; Nurhartanto, Adhi; Sulastri, Sulastri; Nurdianti, Desti; Sutiwi, Sri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The strategic use of language during instruction is essential for creating meaningful interaction between teachers and learners. Forms of communication occurring in the classroom are manifested through speech acts that structure the flow of teaching and learning. Drawing on Searle’s typology, these speech acts may appear as assertives, directives, commissives, expressives, or declarations. This study aims to explore the types and communicative functions of speech acts employed by the teacher in the Speaking 3–Advanced class of the Business and Humanities Study Program at Institut Teknologi Bisnis and Bahasa Dian Cipta Cendikia. Utilizing a qualitative research design, natural classroom interactions were observed and analyzed to capture authentic pedagogical communication. The findings reveal that the teacher produced significantly more utterances than the students, with directive speech acts occurring most frequently. These directives served multiple pedagogical purposes, such as managing classroom procedures, structuring activities, giving instructions, and prompting student responses. The results affirm the teacher’s role not only as a provider of academic content but also as a key manager of classroom discourse through diverse speech act realizations. ABSTRAKPengelolaan bahasa dalam kegiatan pembelajaran memiliki peranan sentral dalam membangun interaksi yang produktif antara guru dan peserta didik. Seluruh bentuk komunikasi di kelas tampak melalui tindak tutur yang digunakan selama proses instruksional berlangsung. Mengacu pada kerangka kategorisasi Searle, tindak tutur dapat diklasifikasikan ke dalam lima bentuk utama, yakni asertif, direktif, komisif, ekspresif, dan deklaratif. Penelitian ini dimaksudkan untuk mengungkap variasi jenis tindak tutur serta fungsi komunikatifnya sebagaimana direalisasikan oleh pengajar pada kelas Speaking 3–Advanced di Program Studi Bisnis dan Humaniora Institut Teknologi Bisnis dan Bahasa Dian Cipta Cendikia. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan observasi langsung terhadap interaksi kelas yang berlangsung secara alami. Berdasarkan hasil temuan, guru mendominasi produksi ujaran dibandingkan mahasiswa. Tindak tutur direktif muncul dengan persentase tertinggi dan berperan dalam mengarahkan kegiatan, menjaga alur pembelajaran, memberikan instruksi, serta memandu tanggapan mahasiswa. Hasil ini menunjukkan bahwa peran guru tidak terbatas pada penyampaian materi, tetapi juga sebagai pengatur interaksi dan pengendali dinamika kelas melalui penggunaan variasi tindak tutur.